Socio- Demographic, Clinical and Lifestyle Determinants of Low Response Rate on a Self- Reported Psychological Multi-Item Instrument Assessing the Adults’ Hostility and its Direction: ATTICA Epidemiological Study (2002-2012) - Tsiampalis, Thomas; Vassou, Christina; Psaltopoulou, Theodora; Panagiotakos, Demosthenes B. (International Journal of Statistics in Medical Research, 2021)
Background: Missing data constitutes a common phenomenon, especially, in questionnaire-based, population surveys or epidemiological studies, with the statistical power, the efficiency and the validity of the conducted analyses being significantly affected by the missing information. The aim of the present work was to investigate the socio-demographic, lifestyle and clinical determinants of low response rate in a self- rating multi-item scale, estimating the individuals’ hostility and direction of hostility. Methods: 3042 apparently healthy volunteers residing in the Athens metropolitan area participated in the ATTICA epidemiological study [1514 (49.8%) were men [46 years old (SD= 13 years)] and 1528 (50.2%) were women [45 years old (SD= 14 years)]]. Hostility and Direction of Hostility was assessed with the Hostility and Direction of Hostility (HDHQ) scale. Binary logistic regression with backward model selection was used in order to identify the key demographic, clinical and lifestyle determinants of higher non-response rate in the HDHQ scale. Results: The vast majority of the participants (87.0%) had missing information in the HDHQ scale. Older age, lower educational level, poorer health status and unhealthy dietary habits, were found to be significant determinants of high nonresponse rate, while female participants were found to be more likely to have missing data in the items of the HDHQ scale. Conclusions: The present work augments prior evidence that higher non-response to health surveys is significantly affected by responders’ background characteristics, while it gives rise to research towards unrevealed paths behind this claim.